Framing of 1Malaysia Development Berhad (1MDB) financial scandal by english and chinese newspapers published in Malaysia - Su-Hie Ting,; Kai-Chee Lam,; Siau-Fan Si,; Kai-Wern Chan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The study compared how the 1Malaysia Development Berhad (1MDB) financial scandal was framed in English and Chinese online newspapers published in Malaysia. Content analysis was conducted for 200 articles for two English newspapers (The Star, 50; Malaysiakini English, 50) and two Chinese newspapers (Sin Chew Daily, 50; Malaysiakini Chinese, 50). The four newspapers were similar in the reliance on episodic framing and government sources of information, and the valence of the articles. Government sources is the opinion leader in 1MDB events but space is given to the voices of the opposition, foreign entities and the public. The English newspapers and Malaysiakini Chinese have more articles with a positive valence (46%-56%) in favour of investigations to resolve the financial corruption case and about 31% of the articles had a negative valence. However, Sin Chew Daily is more critical of the investigations than the other three newspapers. There are significant differences among the newspapers in frame dimensions of news headlines. The responsibility frame is used in close to 80% of the 1MDB articles in the Chinese newspapers but only in 40%-50% of the 1MDB articles in the English newspapers. Instead the English newspapers highlight the economic consequences of 1MDB and the conflict between individuals and groups, as well as contradictions between rumour and fact. The findings suggest that framing of controversial high-profile financial corruption case may differ due to the readership of the English and Chinese newspapers.